Recipe costing : the bottom line - 4 0 16; Miller, Philip; 5 (Hyde Park, NY : Culinary Institute of America)
Examines the components of successful recipe costing, such as the importance of recipes and portion size, the principles behind total recipe costs, an explanation of yields, and using a standardized costing form.
Standard recipes, Portion size, Total recipe cost, Yields Costing form.
Specialized.
Keywords: 2 -- 0; 6; Cost control.;Cost control. -- Food service;Restaurants;Food service management; 20; 2